Inhibitory Effects of Fosmidomycin Against Babesia microti in vitro - Wang, Sen; Li, Muxiao; Luo, Xiaoying; Yu, Long; Nie, Zheng; Liu, Qin; An, Xiaomeng; Ao, Yangsiqi; Liu, Qin; Chen, Jiaxu; Tian, Yu; Zhao, Junlong; et al. (Frontiers in Cell and Developmental Biology, 2020)
Babesia microti, the main pathogen causing human babesiosis, has been reported to exhibit resistance to traditional treatment of azithromycin+Atovaquone and cindamycin+quinine, suggesting the necessity of developing new drugs. Methylerythritol 4-phosphate (MEP) pathway, a unique pathway in apicomplexan parasites, was shown to play a crucial function in the growth of Plasmodium falciparum. In the MEP pathway, 1-Deoxy-D-xylulose 5-phosphate reductoisomerase (DXR) is a rate-limiting enzyme and fosmidomycin (FSM) is a reported inhibitor for this enzyme. DXR has been shown as an antimalarial drug target, but no report is available on B. microti DXR (BmDXR). Here, BmDXR was cloned, sequenced, analyzed by bioinformatics, and evaluated as a potential drug target for inhibiting the growth of B. micorti in vitro. Drug assay was performed by adding different concentrations of FSM in B. microti in vitro culture. Rescue experiment was done by supplementing 200 μM isopentenyl pyrophosphate (IPP) or 5 μM geranylgeraniol (GG-ol) in the culture medium together with 5 μM FSM or 10 μM diminazene aceturate (DA). The results indicated that FSM can inhibit the growth of B. microti in in vitro culture with an IC50 of 4.63±0.12 μM, and the growth can be restored by both IPP and GG-ol. Additionally, FSM is shown to inhibit the growth of parasites by suppressing the DXR activity, which agreed with the reported results of other apicomplexan parasites. Our results suggest the potential of DXR as a drug target for controlling B. microti and that FSM can inhibit the growth of B. microti in vitro.